Glass sword eaudiobook - Aveyard, Victoria (Red Queen, 2016)
The #1 New York Times bestselling series! Perfect for fans of George R.R. Martin's Game of Thrones series, Glass Sword is the high-stakes follow up to the #1 New York Times bestselling Red Queen. Mare Barrow's blood is red—the color of common folk—but her Silver ability, the power to control lightning, has turned her into a weapon that the royal court tries to control. The crown calls her an impossibility, a fake, but as she makes her escape from Maven, the prince—the friend—who betrayed her, Mare uncovers something startling: she is not the only one of her kind. Pursued by Maven, now a vindictive king, Mare sets out to find and recruit other Red-and-Silver fighters to join in the struggle against her oppressors. But Mare finds herself on a deadly path, at risk of becoming exactly the kind of monster she is trying to defeat. Will she shatter under the weight of the lives that are the cost of rebellion? Or have treachery and betrayal hardened her forever? Plus don't miss Realm Breaker! Irresistibly action-packed and full of lethal surprises, this stunning fantasy series from Victoria Aveyard, #1 New York Times bestselling author of the Red Queen series, begins where hope is lost and asks: When the heroes have fallen, who will take up the sword?